Viruses as Complex Adaptive Systems - Solé, Ricard; Elena, Santiago F. (Primers in Complex Systems ;, 2018)
How complex systems theory sheds new light on the adaptive dynamics of viral populationsViruses are everywhere, infecting all sorts of living organisms, from the tiniest bacteria to the largest mammals. Many are harmful parasites, but viruses also play a major role as drivers of our evolution as a species and are essential regulators of the composition and complexity of ecosystems on a global scale. This concise book draws on complex systems theory to provide a fresh look at viral origins, populations, and evolution, and the coevolutionary dynamics of viruses and their hosts.New viruses continue to emerge that threaten people, crops, and farm animals. Viruses constantly evade our immune systems, and antiviral therapies and vaccination campaigns can be powerless against them. These unique characteristics of virus biology are a consequence of their tremendous evolutionary potential, which enables viruses to quickly adapt to any environmental challenge. Ricard Solé and Santiago Elena present a unified framework for understanding viruses as complex adaptive systems. They show how the application of complex systems theory to viral dynamics has provided new insights into the development of AIDS in patients infected with HIV-1, the emergence of new antigenic variants of the influenza A virus, and other cutting-edge advances.Essential reading for biologists, physicists, and mathematicians interested in complexity, Viruses as Complex Adaptive Systems also extends the analogy of viruses to the evolution of other replicators such as computer viruses, cancer, and languages.